Maternal Body Mass Index Does Not Affect Neonatal Umbilical Artery Blood Gas Parameters - Salam E. Chalouhi; Caroline Salafia; Magdy Mikhail; Robert Hecht (Journal of Pregnancy)
This study was undertaken to assess the impact of obesity on fetal well-being in glucose-tolerant and nonhypertensive women. Medical charts of all patients admitted to the labor and delivery department at our institution between January, 2011 and July, 2011 were retrospectively reviewed. Patients with diabetes/impaired glucose tolerance or hypertension were excluded. A total of 100 women, 50 lean and 50 obese, were included. Umbilical artery blood gas parameters (BGPs) were compared in lean (<25 kg/m2) and obese (≥30 kg/m2) women. Obese and lean women were comparable with respect to all baseline characteristics. There was no difference in any of the BGP or Apgar scores between obese and lean patients. Pearson’s correlation coefficient found no significant correlation between BMI and BGP/Apgar scores. Maternal obesity does not seem to affect BGP and fetal well-being in glucose-tolerant and nonhypertensive women.